Neodigitodesmium, a novel genus of family Dictyosporiaceae from Sichuan Province, China - Tian, Wenhui; Chen, Yanpeng; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2022)
A fungus within the family Dictyosporiaceae was isolated from submerged-decaying wood in Sichuan Province, China. Combined ITS, LSU, SSU and tef1 sequence data showed that the species represented a new genus and is described here as Neodigitodesmium cheirosporum gen. et sp. nov. Neodigitodesmium distinct from other genera in the family Dictyosporiaceae based on a hyaline and holoblastic basal connecting conidiogenous cell, conical shaped and smaller with fewer rows (1–4) of conidia. In addition, phylogenetic analysis and morphological comparison showed that the recently introduced genus Paradictyocheirospora is congeneric with Digitodesmium. Based on these results, Paradictyocheirospora is reduced to synonymy under the older generic name Digitodesmium.